THE RIGHT TO READ: A PEDAGOGICAL PRACTICE THAT RECOGNIZES LITERATURE AS A HUMAN RIGHT - Belém dos Santos , Dandara; Macedo Ribeiro, Edinelza; Guilherme Amaral de Abreu, Luis (Revista Gênero e Interdisciplinaridade, 2026)
This article presents the Right to Read project, developed with 6th-grade students at the Irmã-Sá State School, located in the city of Parintins/AM. The project was implemented during the Supervised Internship in Elementary Education II course and aimed to encourage reading through teacher mediation and the exploration of different literary genres. The qualitative research methodology focused on participation and dialogue through activities organized into macro and micro-stages, allowing for the articulation between reading, analysis, interpretation, and creative text production. The theoretical framework engages with Candido (2011), Colomer (2007), and Kiefer (1999), highlighting teacher mediation and reading as a practice of citizenship. As a result of the project, we highlight positive and negative points from the experience gained. On the positive side, we note the advantages of the methodology used, which facilitated the articulation between theory and practice, contributing to the execution of the activities and the observation of a significant improvement in the students’ reading posture. On the negative side, we found that the BNCC (National Common Core Curriculum) is based on an idealized student model, presupposing the prior consolidation of reading skills that, in the reality investigated, were not fully developed. This finding reinforces the criticism that the Base, by standardizing skills and competencies, ends up making invisible subjects who do not fit into this normative path, transferring to the teacher the responsibility of remedying structural gaps in the Brazilian educational system.